2016
DOI: 10.1515/biol-2016-0033
|View full text |Cite
|
Sign up to set email alerts
|

Post-translational modifications of EMT transcriptional factors in cancer metastasis

Abstract: Metastasis is an important reason for death of cancer patients which characterized as the formation of secondary cancers at distant sites. Epithelial– mesenchymal transition (EMT) is a dynamic process that appear to facilitate tumor metastasis in various cancers by switching epithelial cells into mesenchymal properties. Although previous investigation suggested a key role of EMT transcriptional factors in suppression of E-cadherin, the association of these factors with other cellular regulators in cancer metas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…These are the major players of the cell cycle, thus deregulation of their phosphorylation–dephosphorylation state can contribute to cancer progression [160]. Furthermore, phosphorylation of effector proteins, like the TFs Snail, Twist, and ZEB, also contributes to EMT and cancer progression [161].…”
Section: Erk-activating Mutations In the Mapk Signaling Pathway Anmentioning
confidence: 99%
“…These are the major players of the cell cycle, thus deregulation of their phosphorylation–dephosphorylation state can contribute to cancer progression [160]. Furthermore, phosphorylation of effector proteins, like the TFs Snail, Twist, and ZEB, also contributes to EMT and cancer progression [161].…”
Section: Erk-activating Mutations In the Mapk Signaling Pathway Anmentioning
confidence: 99%
“…The other well-known PTM of Twist1 is acetylation [ 151 ]. Studies have revealed that Twist1 interacts with p300 or p300/CBP-associated factor (PCAF), a well-known HAT and promotes EMT by suppressing the expression of E-cadherin [ 152 ] and p53 [ 153 ].…”
Section: Regulation Of the Twist Familymentioning
confidence: 99%
“…This process culminates in the expression of genes with the function of encoding EMT transcription factors (EMT-TFs) [ 4 , 21 , 22 ]. In EMT, three major groups of EMT-TFs play vital roles, including SNAI (Snail and Slug), ZEB (ZEB1 and ZEB2) and TWIST (TWIST1 and TWIST2) [ 23 , 24 , 25 , 26 ], which repress the expression of E-cadherin, thus causing the disassembly of cell–cell junctions and inducing EMT [ 27 , 28 ]. As the main component, TGF-β is also involved in many signaling pathways contributing to the development of EMT, such as the TGF-β signaling pathway [ 29 ], the WNT signaling pathway [ 4 , 30 ], and the Smad Signaling pathway [ 31 , 32 ], which regulates the EMT process.…”
Section: Emtmentioning
confidence: 99%